2021
DOI: 10.5114/aoms.2019.88621
|View full text |Cite
|
Sign up to set email alerts
|

Sarcopenia is associated with increased severe postoperative complications after colon cancer surgery

Abstract: Introduction: Studies have shown that sarcopenia is associated with poor outcomes in patients with gastrointestinal cancer undergoing surgery. We aimed to investigate the relationship between postoperative complications of sarcopenic patients who had been operated on for colon cancer and the effects on short-term mortality. Material and methods: In this study, patients who had undergone colon cancer surgery between January 2013 and December 2018 were collected retrospectively. Sarcopenia was diagnosed by the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…A number of studies have been conducted to evaluate the effects of sarcopenia on the survival of colon cancer patients after surgery, but the findings have been inconsistent. Some studies found that sarcopenia was a predictor for worse OS, 29–38 but some others found that sarcopenia was not associated with OS 39–41 . Discrepancies in the prognostic contributions of sarcopenia might be in part due to differences in the methods used to determine sarcopenia.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have been conducted to evaluate the effects of sarcopenia on the survival of colon cancer patients after surgery, but the findings have been inconsistent. Some studies found that sarcopenia was a predictor for worse OS, 29–38 but some others found that sarcopenia was not associated with OS 39–41 . Discrepancies in the prognostic contributions of sarcopenia might be in part due to differences in the methods used to determine sarcopenia.…”
Section: Discussionmentioning
confidence: 99%
“…Associations between sarcopenia and worse prognosis, such as high postoperative mortality, chemotherapy toxicity, reduced survival, higher infection rates, increased hospital length of stay, and increased mortality, have been pointed out recently [6][7][8][9][10][11][12][13] . Surgical resection in a patient with nonmetastatic colorectal cancer is an important aspect of cancer management, and including the evaluation of sarcopenia as a predictor of perioperative or postoperative morbidity risk can provide prognostic information for surgeons and patients.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the patient's conditions such as skeletal muscle status and fat distribution may influence prognosis after surgery [7,8] . Sarcopenia, defined as the loss of skeletal muscle mass and strength [9] , is currently a hot research topic due to its high prevalence and association with adverse outcomes in patients with various malignancies [7,8,10,11] . The cross-sectional images of computerized tomography (CT) and magnetic resonance imaging (MRI) are now considered standards for muscle mass evaluation [12] .…”
Section: Introductionmentioning
confidence: 99%